1999
DOI: 10.1021/ac980813u
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Mixed-Mode Packing and Voltage Tuning for Peptide Mixture Separation in Pressurized Capillary Electrochromatography with an Ion Trap Storage/Reflectron Time-of-Flight Mass Spectrometer Detector

Abstract: A mixed-mode (reversed-phase/anion-exchange) stationary phase has been used as the capillary column packing for investigation of the separation of peptide mixtures in pressurized capillary electrochromatography (pCEC). This stationary phase contains both octadecylsilanes and dialkylamines. The amine groups of the stationary phase determine the charge density on the surface of the packing and can produce a strong and constant electroosmotic flow (EOF) at low pH. A comparison was made in terms of the capability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…This causes interferences with the detection of the analyte of interest. Thus far, several studies have been performed using packed-CEC/MS [198][199][200][201][202][203][204]. In contrast, only a few studies have been reported on OT-CEC/MS [18,101,121,205].…”
Section: Coupling With Mass Spectrometrymentioning
confidence: 99%
“…This causes interferences with the detection of the analyte of interest. Thus far, several studies have been performed using packed-CEC/MS [198][199][200][201][202][203][204]. In contrast, only a few studies have been reported on OT-CEC/MS [18,101,121,205].…”
Section: Coupling With Mass Spectrometrymentioning
confidence: 99%
“…The concomitant use of pressure assistance increases the mobile phase flow rate to take advantage of the enhanced mass-transfer of the monolithic stationary phases. The influence of pressure in electrically driven chromatography has been investigated by several groups [9,23,35,36]. The combination of the electrophoretic flat flow profile and the pressure-driven parabolic Poiseuille flow profile results in less peak broadening than pressure-driven flow alone.…”
Section: Effect Of Pressure Drop and Buffer Ph On Separation Performancementioning
confidence: 99%
“…The combination of the electrophoretic flat flow profile and the pressure-driven parabolic Poiseuille flow profile results in less peak broadening than pressure-driven flow alone. Tuning of peptide elution by adjustment of the electric field and the inlet pressure has been demonstrated with use of particulate columns [35].…”
Section: Effect Of Pressure Drop and Buffer Ph On Separation Performancementioning
confidence: 99%
“…Lubman and co-workers [146,147] used C 18 or mixed mode packing in the pressurized capillary electrochromatography (pCEC) mode for the peptides analysis. The pCEC affords faster separation of peptides with enhanced resolution, compared to LC.…”
Section: Silica Stationary Phasesmentioning
confidence: 99%
“…Conditions: mobile-phase A, 0.025% TFA B, 0.025% TFA in ACN; gradient of 0-100% B in 40 min; voltage, 1700 V; pressure, 80 bar; columns (a) 85 mm6150 mm packed with C18 reversed-phase and (b) 85 mm6150 mm packed with mixed-mode phase. Reprinted from [147], with permission. demonstrated the potential of the hyphenation CEC-MS for peptide analyses via a nanoelectrospray interface.…”
Section: Silica Stationary Phasesmentioning
confidence: 99%